Bhabinkamtibmas Efforts Through Coaching and Counseling to Prevent theft of Motor Vehicles Cases in the Jurisdiction of the Semarang Police - Fiesta Aulia Rizka (Advances in Police Science Research Journal, 2022)
The rise of the criminal act of theft of motor vehicles in Semarang Regency is a problem that must be addressed immediately. Bhabinkamtibmas as the executor of Binmas Unit is tasked to make preventive efforts to prevent the occurrence of theft of motor vehicle criminal acts, namely by providing public safety messages through coaching and counseling activities to the community. Based on the description, the author is interested in research to know and understand the implementation of coaching and counseling activities, factors that affect the implementation of coaching and counseling activities by Bhabinkamtibmas, as well as efforts made in preventing theft of motor vehicles. The research using this qualitative approach was carried out for two weeks in the jurisdiction of the Semarang Police. The type of research used is field research by lifting data in the field. The data collection technique in this study is carried out in three ways, namely interviews, observations or observations directly, and document studies. Data validation using data triangulation techniques, namely source triangulation, technique, time, and theory. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions and verification. Problems in research are discussed using one theory and five concepts as analytical knives. The theory and concept are management theory, effort concept, Bhabinkamtibmas concept, coaching and extension concept, prevention concept, and motor vehicle theft concept. The data sources or information in this study were obtained from primary and secondary data sources. Primary data sources are obtained by interview techniques and observations directly of research objects, while secondary data sources are obtained using document studies. The findings obtained during the study, several factors hinder the quantity and quality of personnel is not adequate when compared to the burden of Bhabinkamtibmas duties. The majority of Bhabinkamtibmas members have not attended vocational education. The method used is still not maximal and the material submitted is still general. On the other hand, supporting factors in the form of budget and the facilities and infrastructure provided have not been used optimally. Based on the findings, the authors suggest that personnel be added and improve the competence of Bhabinkamtibmas personnel by participating in vocational training or education.